REDETERMINING HALAL LIFESTYLE: A QURAN PERSPECTIVE - Adib Susilo; Muhammad Kurnia Rahman Abadi; Setiawan Lahuri; Rizal Achmad (IAIN Manado, 2022)
This study aims to explore the verses in the Al-Qur'an which discuss the halal lifestyle which is the main resource for Muslims in everyday life. The method used in this study is a qualitative method with a library research approach which was carried out to explore the interpretation of the Qur'an about the halal lifestyle from the holy book, the Al-Qur'an. This study found that the halal lifestyle based on the perspective of the Qur'an can be continued in the aspect of consumption or lifestyle in choosing food, namely choosing between food, medicine, and products that are forbidden containing alcohol or pork, or choosing Food that is lawful in Islam, the food that is halal and?tayyib. It is the same also in the aspect of Muslim fashion, halal travel, and tourism, as well as in the fields of finance and charity. This research focuses on exploring the most common and familiar lifestyles practiced by the current generation. Further study of the details or even the digital lifestyle should be carried out by future research.